Inovasi Pembelajaran Science, Technology, Religion, Engineering, Art, and Mathematics Pada Mata Pelajaran Pendidikan Agama Islam - Iwan Sanusi; Hasbiyallah Hasbiyallah; Mahlil Nurul Ihsan; Afrillia Muthia Rahman (Jurnal Perspektif, 2022)
The development and progress of the times always demands change and innovation, including in the education and learning sector of Islamic Religious Education. The purpose of this study is to discuss theoretically and practical findings about integrated learning, namely innovation learning STREAM (Science, Technology, Religion, Engineering, Art, and Mathematics) in Islamic Religious Education subjects. This type of research is qualitative with analytical descriptive approach, uncovering findings and literature study. The findings show that Islamic Religious Education learning at SMAN 5 Bandung in class XII on the Basic Competence of Marriage in Islam, has been carried out using the STREAM approach in four meetings, and collaborates with the subjects of Cultural Arts, Crafts and Entrepreneurship, Sundanese Language, Civics, Biology, Economics-Accounting, and Mathematics. The learning model used is Project Based Learning (PjBL), Role Playing, Time Line of the River of Life and Presentation-Discussion. The products produced are in the form of power point teaching materials, photos and videos of marriage practice simulations with walimah (reception), as well as graphic info on time line planning for life targets until the estimate returns to Allah SWT.